(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2023)
In this work, some of the paremias used by Sempronio in La Celestina will be analyzed, given the determining function that these structures of a sententious nature fulfill in the work. On the other hand, there are so many paremias present that, as Pier Luigi Crovetto maintains (cfr. Rojas, 1995: XXV), we are witnessing the construction of a “text within the text”, of a “collettore di sapienze”. The most obvious conclusion is to consider Tragicomedy as the perfect synthesis of an era, which incorporates a paremiological universe, on which to highlight the excesses of the antiheroes themselves. On the other hand, it is intended to highlight the different translation techniques (Corbeta Melchor, 2000) that the translators considered (Hordóñez and Brichetti) respect when translating La Celestina into Italian. Likewise, it is interesting to observe that translators do not always detect paremiological units in the source language and resort to literality, making the mistake that the paremia loses the idiomatic valu.